Inventory Demand and Cost of Capital Effects - Lieberman, Charles (The Review of Economics and Statistics, 1980)
T HEORETICAL models of inventory inl vestment including Belsley (1969), Holt et al. (1960), Whitin (1953) and others invariably suggest the opportunity cost of inventories should be included as a key explanatory variable in any empirical study of inventory behavior. In the absence of an opportunity cost (or other holding costs), the theoretically optimal inventory holding is infinitely large. Even so, it is rather rare any financial variable emerges as statistically significant in empirical studies of inventories.1 Michael Lovell, who has written extensively on inventory investment, goes so far as to comment that the probability of obtaining an interest-rate coefficient with negative sign is 50 percent (1976, p. 400). Even the MITPennsylvania-Social Science Research Council model, which represents an explicit attempt to specify in detail the channels of monetary policy, fails to include monetary variables in its inventory equation.2 The absence of empirical evidence in support of a cost of capital effect on inventory investment renders uncertain what many economists regard as a major channel of monetary policy. It is often commented roughly three quarters of the variance in GNP is accounted for by changes in inventory investment. Since monetary policy is commonly viewed as very powerful, it is truly remarkable so little econometric evidence exists to indicate a cost of capital effect on the most variable component of GNP. This study attempts to re-examine the size and significance of the theoretically important cost of capital effect on inventory investment by utilizing firm specific cost of capital measures, as suggested by the finance theory literature, in a pooled cross section econometric analysis of inventory behavior. The cost of capital measure is computed using the actual balance sheet capitalization particular to each firm in the sample for each point in time. Use of a firm specific cost of capital measure instead of a market interest rate avoids the measurement errors introduced into the analysis by the latter procedure. Risk differences among firms, such as between General Motors and Chrysler, imply substantial differences in capital costs. The errors in measurement problem introduced by a market interest rate will bias towards zero the cost of capital effect. Thus a firm specific cost of capital measure may serve as a more effective opportunity cost variable in an econometric analysis of inventory investment. Perhaps even more critical than the use of firm specific cost of capital measures, the econometric analysis is conducted using two samples of firms with each sample disaggregated by stage of fabrication. The first sample, which includes heavy machinery producing companies, attempts to explain inventory investment behavior for companies produce output in response to orders. The second sample consists of textile companies produce output predominantly to stock in anticipation of orders. Aggregation of firms produce to stock and produce to order-and, in addition, aggregation of inventories across stages of fabrication-may obscure the underlying behavioral characteristics operate, in fact, at the individual firm level. As suggested by theory, the findings of this study indicate the cost of capital is a highly sigReceived for publication May 30, 1978. Revision accepted for publication October 30, 1979. * Federal Reserve Bank of New York. A preliminary draft of this paper was presented at the August 1978 meetings of the Econometric Society in Chicago, Illinois. Financial support for the formative stages of this research was provided by the Computer Science Center of the University of Maryland and from the University Research Board in the form of a faculty research award. The data were provided by the College of Business and Management of the University of Maryland. The author thanks Clopper Almon, Robert Eisner, Irwin Friend, Robert J. Gordon and Joel Popkin for their comments and David Dossetter for very able research assistance. Neither they nor the Federal Reserve Bank of New York nor the Federal Reserve System are responsible for the errors or views contained in this paper. I Studies by Kuznets (1964) and Liu (1963) are among the very few report statistically significant interest rate effects. 2 The paucity of econometric evidence on behalf of cost of capital effects is nevertheless consistent with the prewar survey of Meade and Andrews (1938) (and others) and the postwar surveys of Crockett, Friend and Shavell (1967) and Shavell and Woodward (1971), which questioned managers on the degrees to which they adjusted inventories in response to changes in financial conditions.